Congenital Corrected Transposition of Great Arteries in Adults with Varied Presentation - Akshay Narendra Kotasthane; Susheel K. Malani; Chigullapalli Sridevi; Digvijay D Nalawade (Journal of the Practice of Cardiovascular Sciences)
Congenital corrected transportation of great arteries (ccTGA) is a rare congenital heart disease, accounting for < 1% of congenital heart diseases. It remains undiagnosed until adulthood, in the absence of associated congenital anomalies. Adults with ccTGA are usually asymptomatic or their diagnosis may be missed during initial evaluation. It is sometimes diagnosed inadvertently while evaluating a murmur or a low heart rate. We aim to report three cases of ccTGA with varied presentations. We presented three cases of ccTGA with varied presentation, two cases of complete heart block requiring permanent pacemaker, out of which one had situs inversus totalis with levocardia, the other had situs solitus. The 3rd case was presented as case of ccTGA with heart failure with viseroarterial situs solitus, large atrial septal defect, large inlet ventricular septal defect, and severe pulmonary stenosis and had undergone bidirectional Glenn shunt. These cases illustrate the challenges confronted in adult practices when patient with unrecognized ccTGA presents during initial visits. Congenital corrected transposition of great arteries is rare congenital anomaly that poses a challenge in adulthood due to its varied presentation. Thus, an increased awareness about key diagnostic features is crucial for early recognition of ccTGA and its effective management.